Identification of gadget usage patterns and their impact on children's mental health using a local cultural approach in Ciamis Regency - Dini Nurbaeti Zen; Daniel Akbar Wibowo; Asep Wahyudi; Irfan Permana; Bunga Maratun Nailla; Septian Firmansyah; Nina Deswinta (Science Midwifery, 2025)
The development of digital technology has brought significant changes to children's behavior, including in Ciamis Regency. Gadgets such as smartphones and tablets are now part of children's daily lives, both for entertainment and learning. However, excessive use without parental supervision can have various negative impacts on children's mental health, such as sleep disturbances, emotional changes, and decreased social interaction. This study aims to identify gadget usage patterns and their impact on children's mental health, as well as explore the potential of local cultural values ​​as a promotive and preventive approach in maintaining children's psychosocial balance in the digital era. This study uses mixed methods with an explanatory sequential design, namely a quantitative analysis is carried out first to map the conditions of gadget use and mental health of school-aged children, then continued with a qualitative approach to explain the quantitative findings in more depth. In the quantitative stage, 60 children aged 7–12 years in Ciamis Regency were selected as respondents from the educational units that served as the research location. The instruments used were a questionnaire on gadget usage patterns and a mental health assessment instrument. Data analysis was carried out descriptively, cross-tabulation, and continued with ANOVA tests to determine the effect of gadget use on children's mental health. The results of the study showed that the majority of children were in the 9–11 year age range, a period of cognitive and psychosocial development that is highly sensitive to environmental stimulation. Gadget usage patterns showed that 50% of children were in the moderate usage category, while 36.7% were in the problematic usage category. The duration of gadget use was dominated by more than three hours per day with main activities such as watching YouTube, accessing TikTok, playing online games, and communicating via WhatsApp. Factors triggering high gadget use include busy parents, low supervision, and the use of gadgets as a tool to calm children. In terms of mental health, it was found that 43.3% of children were in the problematic category and 40% were in the borderline category, indicating a fairly concerning condition. Frequently reported symptoms included sleep disturbances, irritability, anxiety, decreased concentration, and withdrawal from social interactions. ANOVA analysis showed a p-value = 0.000, indicating a significant influence between gadget usage patterns and mental health. In other words, the more intense gadget use, the higher the risk of children experiencing mental health disorders. These findings align with previous research showing a strong link between excessive digital device use and increased symptoms of anxiety, depression, and social dysfunction in children and adolescents (Holmes et al., 2021; Odgers & Jensen, 2020).The qualitative phase was conducted through in-depth interviews with 21 informants consisting of parents and teachers. The analysis technique used was thematic analysis. The qualitative results revealed two major themes: (1) the emergence of psychological symptoms due to excessive gadget exposure and (2) changes in children's social behavior. Informants described that children became irritable when asked to stop playing with gadgets, were less interested in physical activities, and reduced interaction with peers. They preferred digital activities to traditional games or studying. Interviews also showed that local values ​​such as silih asih (compassion), silih asah (grooming), and silih asuh (caregiving) are still recognized, but have not been consistently integrated into parenting patterns and therefore have not been able to become a strong protective factor against the impact of gadget use. Overall, this study concludes that school-age children in Ciamis Regency are a group vulnerable to mental health problems related to gadget use. The mixed methods used provide a comprehensive picture that problematic gadget use patterns are directly proportional to the increased risk of mental health problems. Therefore, family-based interventions, schools, and local wisdom are important strategies in reducing the negative impacts of gadget use and supporting children's mental development.